Determinants of Academic Performance of Primary Teachers’ College Students in South-Western Uganda - Nuwagaba, James; Mwesigye, Adrian Rwekaza; Karoro, Emmanuel (East African Journal of Education Studies, 2022)
The purpose of the research was to establish the perceived determinants of academic performance of primary teachers’ College (PTC) students in South Western Uganda. The researchers anchored on social constructivist philosophy adopted a cohort longitudinal survey research design incorporating description techniques. The researchers employed qualitative methods of data collection and analysis. Data was collected from the nine government-aided PTCs in South Western Uganda. The sample size was 298 comprised of 214 students randomly selected from the nine PTCs and 72 tutors, nine PTC principals, two officials from Kyambogo University, and one official from the Ministry of Education and Sports purposively selected. Data was collected using unstructured questionnaires, interview guides, focus group discussion guides, and documentary analysis guides. Research findings revealed that respondents perceived the academic performance of PTC students in South Western Uganda as determined by an interplay of various factors under nine themes namely; administration, learning environment, tutors, study materials, time, students’ background, welfare, assessment, and study practices. This implies that if the college administration is effective, the learning environment is conducive, tutors demonstrate professionalism, study materials are available, adequate time is given to the program, students with the good background are admitted, there is improved students’ welfare, proper assessment is conducted and students are always engaged in study practices which support learning, there would be improved academic performance of students in PTCs in South Western Uganda. The conclusion drawn from the findings and other researchers was that there are several factors that determine academic performance in PTCs but much depends on the personality and leadership competencies of the college principal. It was recommended that principals of PTCs should be helped to apply leadership styles that enable all other factors that determine academic performance to thrive.
Keywords: Determinants; Academic Performance; Students; Primary Teachers’ Colleges; South Western Uganda